2006
DOI: 10.1088/0031-9155/51/9/003
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index of carcinogen-induced rat mammary tumours

Abstract: Near-infrared optical techniques for clinical breast cancer screening in humans are rapidly advancing. Based on the computational inversion of the photon diffusion process through the breast, these techniques rely on optical tissue models for accurate image reconstruction. Recent interest has surfaced regarding the effect of refractive index variations on these reconstructions. Although many data exist regarding the scattering and absorption properties of normal and diseased tissue, no measurements of refracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 65 publications
1
50
0
Order By: Relevance
“…These previous studies have shown that breast cancer appears more highly scattering than healthy tissue and disrupts the normal structure of adipose and stroma found in the breast. However, solid invasive tumors may be difficult to distinguish from islands of fibrous stromal tissue [19,28]. This may be due to a lack of clear structures and similar refractive indices [28].…”
Section: Introductionmentioning
confidence: 99%
“…These previous studies have shown that breast cancer appears more highly scattering than healthy tissue and disrupts the normal structure of adipose and stroma found in the breast. However, solid invasive tumors may be difficult to distinguish from islands of fibrous stromal tissue [19,28]. This may be due to a lack of clear structures and similar refractive indices [28].…”
Section: Introductionmentioning
confidence: 99%
“…To find the field scattered to the pinhole by the sample, we consider the field u(r) in the object space V. The field satisfies the inhomogeneous reduced wave equation: (1) where k is the free-space wavenumber of the field, n 0 (r) is the refractive index representing the optical system of Fig. 1 without an object, and n(r) is the inhomogeneneous refractive index of the object, which is treated as a perturbation on the order of a small parameter ε.…”
Section: Derivation Of Refractive Index Reconstruction Relationmentioning
confidence: 99%
“…However, few instruments are able to probe the group refractive index of media at the micrometer scale. Recent work [1] has indicated that the group refractive index has potential diagnostic capability to distinguish breast cancer from normal tissues. To be able to further investigate the origin of the group refractive index contrast at the scale of organelles, we propose a new instrument.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In biological sciences, refractometry was employed to determine salinity levels due to total plasma protein (TPP) in fish blood samples 1 and in avian species, 2 to study the molecular basis of virus entry by analyzing the interactions between cellular receptors of herpes virus and the viral glycoproteins in a molecular level, 3 to evaluate the purity and the quality of antimalarial drugs, 4 to rapidly measure glucose concentration in blood, 5,6 and to diagnose and evaluate the evolution of tumors in breast tissues. 7 By performing refractive index measurements, the study of bubble flow, 8 as well as the characterization of optical, 9 polymeric, 10,11 and chemical 12,13 materials can be carried out. For such a large variety of applications many refractometry devices were proposed and developed concerning the particularities of each application.…”
Section: Introductionmentioning
confidence: 99%